High-resolution, non-contact, cellular level imaging of the cornea of the eye in vivo. (June 2022) - Suchand Sandeep, C.S.; Chan Lwin, Nyein; Liu, Yu-Chi; Barathi, Veluchamy Amutha; Aung, Tin; Baskaran, Mani; Murukeshan, Vadakke Matham
Highlights: Non-contact, cellular level imaging of the cornea of the eye. High-resolution, in vivo imaging demonstrated in preclinical animal models. Real-time imaging, without the need for any image processing. Polarization scheme utilized to reduce coherent artefacts. Upright positioning and the use of NIR light ensures patient comfort. Abstract: Corneal diseases, along with glaucoma and cataract, are the leading causes of blindness worldwide. While corneal surgery offers good success rates, early diagnosis and disease prevention is the preferred choice over expensive and complex surgical procedures. Non-contact, high-resolution imaging modalities for imaging the corneal structures are highly desirable for clinical examinations for early diagnosis of corneal diseases. The currently used clinical standard is the in vivo confocal laser scanning microscopy, which is a contact based method. In this context, an in-house developed, non-contact, Gaussian epi-illumination based imaging system was used to image corneal injury in preclinical animal models in vivo . New Zealand white rabbits and Wistar rats were used as the preclinical models for the investigations. The lateral resolution of the developed system is 1.1 μm. The images obtained with the developed system, as well as the dimensional information of the corneal structures, are in good agreement with the data previously reported using standard methods. The proposed system offers a simple, easy operable, real-time, non-contact imaging modality for the evaluation of corneal structures in high-resolution.